University and Reading: A Critical Look at the Measurements of the Reading Habit - Barrios Andrade, Diego Fernando (Rastros Rostros, 2023)
This article addresses as a problem of inquiry the fact that the reading habit is far from being preached by an absolute proportion of university students. That is to say, still a large sector of the students does not have this habit as expressed in multiple investigations. In this sense, it is argued that the low reading rates in higher education are due to a non-rigorous commitment of the different subjects to reading. In particular, the special way in which each subject outlines its own learning objectives, which do not have to use reading radically, leads to the habit of reading not being strictly encouraged as it is in those classes where it is essential to read. Likewise, the methodological perspective assumes an analytical-comparative approach with which it seeks to articulate a duality of functions: on the one hand, a review and examination of the literature and, on the other, an ordered reflection on its fundamental content. As a conclusion, it must be said that the university is not spreading the habit of reading as it would be expected to do through the curriculum and, consequently, it is still necessary to rethink transversal policies to the curriculum that promote reading in the university.
Keywords: education; university students; reading habit; university